2006
DOI: 10.1021/la061215a
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Photodimerization of Cinnamic Acids in Water:  Templation with Cucurbiturils

Abstract: Cinnamic acids upon irradiation in solution undergo geometric isomerization while dimerizing to different dimers in the crystalline state. Controlling the nature of the dimer formed upon irradiation remains a challenging task. We have aligned a variety of cinnamic acid molecules in a head-head fashion employing cucurbit[8]uril, a weakly water soluble host as a template. The water solubility of cucurbit[8]uril is enhanced by inclusion of water soluble cinnamic acids and positions the olefins in an arrangement t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 21 publications
7
76
0
Order By: Relevance
“…188 Ramamurthy and coworkers carried out another impressive set of experiments. [189][190][191][192] By irradiation of different olefins (13)(14)(15) encapsulated in CB8 in aqueous solution, the syn dimer was obtained in 90% yield (16a), while irradiation of the 1 : 2 host-guest complex in the solid state showed no dimerization even after two days. 191,192 When these reactions were carried out without CB8, phenanthroline (17), the cis-isomer (18), and the hydration product (19, major product) were formed instead.…”
Section: Photochemical Reactions Catalyzed or Templated By Cbnmentioning
confidence: 99%
See 1 more Smart Citation
“…188 Ramamurthy and coworkers carried out another impressive set of experiments. [189][190][191][192] By irradiation of different olefins (13)(14)(15) encapsulated in CB8 in aqueous solution, the syn dimer was obtained in 90% yield (16a), while irradiation of the 1 : 2 host-guest complex in the solid state showed no dimerization even after two days. 191,192 When these reactions were carried out without CB8, phenanthroline (17), the cis-isomer (18), and the hydration product (19, major product) were formed instead.…”
Section: Photochemical Reactions Catalyzed or Templated By Cbnmentioning
confidence: 99%
“…192 Ramamurthy further extended this chemistry to include the photodimerization of neutral guests, such as trans-cinnamic acid (20). 189,190 Upon irradiation of 20 encapsulated by CB8 (in aqueous solution as well as in the solid state), the reaction afforded the syn head-to-head dimer (21), along with the corresponding cis isomer (22). 189 The latter was formed as dominant product in the presence of the smaller CB7.…”
Section: Photochemical Reactions Catalyzed or Templated By Cbnmentioning
confidence: 99%
“…[10] Urbach examined the potential for Q [8]·MV (methyl viologen) to recognize N-terminal tryptophan in aqueous solution. [5] Ramamurthy and co-workers [11] found that Q [8] mediates inter-molecular photodimerization of cinnamic acid, trans-1,2-bis(n-pyridyl)ethylenes, and stilbazoles. In the above-mentioned work, we noticed that at least one aromatic group of each guest molecule was situated in the cavity of Q [8].…”
Section: Introductionmentioning
confidence: 99%
“…2.7 ). 21,22 As noted in the introduction, cinnamic acids give solid -state photoproducts that depend on the crystal lattice and generally lead to the ineffi cient formation of mixtures of photocycloadducts when irradiated in fl uid solutions (predominantly truxinic acids, i.e., HH dimers). 23 Cucurbit[ n ]urils (CB[n]) and calix[ n ]arenes (CA[ n ]) are obtained from the condensation of glycouril and phenols with formaldehyde, respectively, and are in many ways related to the CD hosts described above, presenting hydrophobic pockets in which to encapsulate guests.…”
Section: Templated (2 π + 2 π ) Photocyclization Reactions In Solutionmentioning
confidence: 99%